THE EFFECT OF IMPLEMENTING THE COOPERATIVE LEARNING MODEL LISTENING TEAM ON STUDENTS’ ACTIVE PARTICIPATION IN CLASS VIII AT SMPN 1 TAROGONG KALER - Asep Nurhidayat; Ade Suherman; Prima Melati (Institut Pendidikan Indonesia, 2026)
This research was motivated by the fact that most students in class VIII B of SMPN 1 Tarogong Kaler still appeared passive during the learning process, as the Civics (PKn) teacher at the school still employed the lecture method. The purpose of this research was to determine the active participation of students in class VIII B of SMPN 1 Tarogong Kaler in the Civics subject. The research method used was an experimental method with a One-Group Post-Test Only Design. Data collection techniques included observation and questionnaires. The sampling method used in this study was non-probability sampling with a purposive sampling technique. The population of the study consisted of all eighth-grade students, totaling 427 individuals, and the sample used was class VIII B with 40 students. The results of the study can be summarized as follows: (1) The implementation of the cooperative learning model Listening Team in the Civics subject increased students' active participation by creating a more interactive and enjoyable learning atmosphere, improving students' memory and collaboration, thus resulting in more effective learning. (2) There was a significant change in students’ active participation after applying the Listening Team cooperative learning model, as indicated by the regression test results showing a regression coefficient of 0.474 or 47.4%, meaning that there was an increase in students’ active participation after the model was implemented. (3) There was a significant influence of the implementation of the Listening Team cooperative learning model on students' active participation. This was evidenced by the analysis results showing a significance level lower than 0.05, which means that the application of the Listening Team model had an effect on the active participation of students in class VIII B of SMPN 1 Tarogong Kaler. Keywords: Cooperative Learning Model Listening Team, Active Participation, Civics Education